PENGARUH ARUS KAS OPERASI, LABA BERSIH, UKURAN PERUSAHAAN DAN PRICE BOOK VALUE TERHADAP HARGA SAHAM - Heriston Sianturi; Anji Angger Bimo Setyo Wibowo (Fakultas Ekonomi dan Bisnis Universitas Satya Negara Indonesia, 2022)
This research was a puspose to provide empirical eviden about operating cash flow, net income, SIZE firm and stock market value that effect to the stock price. The ratio in this research were AKO, Earning After Tax (EAT), SIZE (Ln Tottal Asset), and Price to Book Value (PBV) as independent variables and stock price as dependent variable. The samples of this research are LQ45 Index company that being active are traded and listed in BEI 2016-2019. Moreover, it is chosen by purposive sampling whereas it is based on some criteria. The statistic method used to test on the research hypothesis is multiple liniear regression. The result show that AKO, Earning After Tax (EAT), SIZE (Ln Tottal Asset), and Price to Book Value (PBV) simultaneously are significant in prediction the stock price which will be traded. This research also indicate that AKO, Earning After Tax (EAT), and SIZE (Ln Tottal Asset) partial are significant in prediction the stock price which will be traded. Keywords : Operating Cash Flow, Net Income, SIZE Firm, Price Book Value, and Stock Price.